Board Gender Diversity, Corporate Productivity and ESG Performance - Liu, Yi; Li, Yi (Journal of Global Economy, Business and Finance, 2024)
This study is based on the two major strategies of new productivity and corporate ESG development, using data from China's A-share listed companies from 2011 to 2022 to empirically test the impact of female directors on corporate ESG performance, and the impact of corporate new productivity development on both. potential role. Research results show that the presence of female directors has a positive effect on improving corporate ESG; the development level of corporate new productivity can strengthen the positive impact of female directors on corporate ESG. In addition, further heterogeneity analysis found that in companies with strong profitability, female directors and corporate new productivity have a more significant role in promoting ESG.